2013
DOI: 10.1021/am401102h
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Approaches for Converting a Wood Hydrolysate to High-Quality Barrier Coatings

Abstract: An advanced approach for the efficient and controllable production of softwood hydrolysate-based coatings with excellent oxygen-barrier performance is presented. An innovative conversion of the spray-drying technique into a coating applicator process allowed for a fast and efficient coating process requiring solely aqueous solutions of softwood hydrolysate, even without additives. Compared to analogous coatings prepared by manual application, the spray-drying produced coatings were more homogeneous and smooth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Excellent gas barriers of hemicelluloses make them suitable for coatings and films in the food packaging field [18][19][20]. However, two obvious drawbacks of hemicelluloses need to be overcome, that is, the typical brittleness [10,21] and the inherent hydrophilicity [10,22]. Several methods are commonly used to improve the performance of hemicelluloses films, including adding a certain amount of plasticizers (sorbitol, glycerol, and xylitol) in hemicelluloses solution [23,24], in the presence of plasticizers, mixing hemicelluloses and other natural polymers (starch, chitosan, cellulose nanofibers, lignin, carboxymethyl cellulose, and sodium alginate) [3,22], and chemical modification of hemicelluloses (esterification, etherification, cross-linking, and graft copolymerization) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Excellent gas barriers of hemicelluloses make them suitable for coatings and films in the food packaging field [18][19][20]. However, two obvious drawbacks of hemicelluloses need to be overcome, that is, the typical brittleness [10,21] and the inherent hydrophilicity [10,22]. Several methods are commonly used to improve the performance of hemicelluloses films, including adding a certain amount of plasticizers (sorbitol, glycerol, and xylitol) in hemicelluloses solution [23,24], in the presence of plasticizers, mixing hemicelluloses and other natural polymers (starch, chitosan, cellulose nanofibers, lignin, carboxymethyl cellulose, and sodium alginate) [3,22], and chemical modification of hemicelluloses (esterification, etherification, cross-linking, and graft copolymerization) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure C, natural loofah presented four characteristic peaks at 3400, 2900, 1730, and 1636 cm –1 . The peak located at 1730 cm –1 was attributed to the presence of hemicellulose . For pretreated loofah, the disappearance of the peak suggested that hemicellulose could be detached by the pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…The peak located at 1730 cm −1 was attributed to the presence of hemicellulose. 52 For pretreated loofah, the disappearance of the peak suggested that hemicellulose could be detached by the pretreatment. For the loofah before and after pretreatment, the peaks attributed to O−H, C−H, and COO− vibrations at 3400, 2900, and 1636 cm −1 , respectively, suggested that the chemical structure of loofah cellulose was not damaged by the pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, spray drying has been used to produce coatings 34 and microparticles 35 due to its efficiency, high yield, and reproducibility. Here, a chemical cross-linking process during spray drying was developed to produce hemicellulose microgels to achieve value-added and renewable products.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Spray drying offers advantages such as efficiency, high yield, reproducibility, and more controllable distribution of particle size compared with other particle fabrication techniques. , Thus, the production of spray-dried microparticles has gained interest and is widely used in the pharmaceutical, food, and chemical industries. , Spray drying has been used to produce a reproducible coating layer of hemicellulose particles on polyethylene terephthalate substrates, stereocomplexed particles of a poly­(lactic acid) and poly­( d -lactide) polymer blend, and inorganic particles consisting of a mixed Ti/Al 2 O 3 as a functional artificial tooth root . It has also been used to modify calcium phosphate bone cement composites and to fabricate antigen-loaded porous polyelectrolyte microparticles for use in oral antigen delivery .…”
Section: Introductionmentioning
confidence: 99%